2013
DOI: 10.3109/01902148.2013.819535
|View full text |Cite
|
Sign up to set email alerts
|

Analysis ofEGFR,EML4-ALK,KRAS, andc-METmutations in Chinese lung adenocarcinoma patients

Abstract: Most Chinese lung adenocarcinoma patients harbor driver gene mutations, among which ALK rearrangements were more common in Hunan patients than in previously reported populations. Future clinical trials should be conducted to determine the safety and efficacy of drug combination targeting different driver mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 44 publications
3
45
1
Order By: Relevance
“…The mutation rates in Chinese population were much higher in adenocarcinomas, females, or never-smokers, ranging from 45% to 61% [1,32,44,46]. Similar to these reports, we have found that EGFR mutations were more frequently observed in females (63.5% vs. 28.1% in males), never-smokers (55.7% vs. 26.2% in ever smokers), and adenocarcinomas (49.5% vs. 2.6% in squamous cell carcinomas) in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation rates in Chinese population were much higher in adenocarcinomas, females, or never-smokers, ranging from 45% to 61% [1,32,44,46]. Similar to these reports, we have found that EGFR mutations were more frequently observed in females (63.5% vs. 28.1% in males), never-smokers (55.7% vs. 26.2% in ever smokers), and adenocarcinomas (49.5% vs. 2.6% in squamous cell carcinomas) in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…EML4-ALK rearrangement was reported as a relatively low frequent rearrangement ranging from 1.5% to 6.7% among unselected Caucasian NSCLC patients (14)(15)(16)(17). It seems to have higher frequency in Asian population, and was reported as high as 5.1-10% (18)(19)(20)(21). Part of the explanation was that in those studies, patients were selected from EGFR wild population.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it will be important in future studies to assess the occurrence of the Δ7–8 mutation in paired samples of primary and recurrent tumors after MET antibody-based therapies, but also anti-EGFR therapies since cells may use MET Δ7–8 to bypass EGFR signaling [3, 53]. With this in mind, the use of specific tyrosine kinase inhibitors of MET may have preference over antibody-based therapy for resistant tumors, at least in the ones that are KRAS and RAF wild type, [3, 21, 57, 61] since MET Δ7–8 is sensitive to these inhibitors [42]. Such inhibitors have already shown to improve overall survival of patients with non-small cell lung carcinoma with MET amplification and renal papillary carcinoma with MET mutations [11, 45].…”
Section: Discussionmentioning
confidence: 99%